2019
DOI: 10.1111/aji.13201
|View full text |Cite
|
Sign up to set email alerts
|

Altered cord serum 25‐hydroxyvitamin D signaling and placental inflammation is associated with pre‐term birth

Abstract: Problem Vitamin D is well‐known for having anti‐inflammatory and immunomodulatory properties. Impaired maternal vitamin D status has been known to increase the risk of adverse pregnancy outcomes like pre‐term birth. The present study aims to evaluate the impact of fetal cord serum 25‐hydroxyvitamin D‐mediated signaling in mediating inflammatory responses in placenta during pre‐term birth. Method of study For the above purpose, cord serum 25 hydroxyvitamin D 25(OH)D were measured in term (n = 20) and pre‐term (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
9
0
2
Order By: Relevance
“…In contrast, a cohort of pregnant women from the US reported maternal vitamin D was associated with higher newborn weight and head circumference but not with placental weight 58 . However, an Indian study showed that insufficient cord serum 25(OH)D enhanced placental inflammation in neonates born preterm 59 . Authors suggested that the decreased expression of vitamin D receptor and cathelicidin anti-microbial peptide in placentae from preterm birth neonates in their study may have contributed to placental inflammation 59 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, a cohort of pregnant women from the US reported maternal vitamin D was associated with higher newborn weight and head circumference but not with placental weight 58 . However, an Indian study showed that insufficient cord serum 25(OH)D enhanced placental inflammation in neonates born preterm 59 . Authors suggested that the decreased expression of vitamin D receptor and cathelicidin anti-microbial peptide in placentae from preterm birth neonates in their study may have contributed to placental inflammation 59 .…”
Section: Discussionmentioning
confidence: 99%
“…However, an Indian study showed that insufficient cord serum 25(OH)D enhanced placental inflammation in neonates born preterm 59 . Authors suggested that the decreased expression of vitamin D receptor and cathelicidin anti-microbial peptide in placentae from preterm birth neonates in their study may have contributed to placental inflammation 59 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Budhwar et al reported that VD deficiency disturbed homeostasis of the inflammatory response in the placenta, activating the cytokine network and followed by spontaneous premature preterm delivery [57]. At the same time, Dutra et al observed a correlation between maternal VD levels and VDR gene polymorphisms, as well as the risk of premature birth [58].…”
Section: Vdr Protein Level In Placentasmentioning
confidence: 99%
“…Thus, HMGB1 may play a role in cervical ripening as increased gene expression of HMGB1 has been detected in cervix from preterm mothers 80 . PTB may also occur due to decreased levels of the anti‐inflammatory molecule vitamin D within cord serum, which may trigger inflammation by increasing proinflammatory molecules such as HMGB1 in the placenta 81 . In addition, patients who suffer from intra‐amniotic inflammation deliver early when subjected to high concentrations of HMGB1 and IL‐6 within the amniotic fluid 82 .…”
Section: The Role Of Hmgb1 Throughout Gestationmentioning
confidence: 99%